2020
DOI: 10.5213/inj.2040010.005
|View full text |Cite
|
Sign up to set email alerts
|

Underactive Bladder; Review of Progress and Impact From the International CURE-UAB Initiative

Abstract: There is a significant need for research and understanding of underactive bladder (UAB). The International Congress of Urologic Research and Education on Aging UnderActive Bladder (CURE-UAB) was organized by Doctors Michael Chancellor and Ananias Diokno in order to address these concerns. CURE-UAB was supported, in part, by the US National Institute of Aging and National Institute of Diabetes Digestive and Kidney. Since 2014, there have been 5 successful CURE-UAB congresses. They have brought together diverse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 22 publications
(23 reference statements)
0
18
0
Order By: Relevance
“…Thus, urinary retention/stress incontinence/poor bladder compliance may be induced as a result of lower spinal cord injury or peripheral nerve injury, which causes LMN dysfunction. Detrusor sphincter dyssynyergia, autonomic dysreflexia, and detrusor overactivity may occur in response to UMN dysfunction or cerebral injuries ( Chancellor et al, 2020 ). The problems that can arise as a result of cerebral injuries that cause sensory neuron dysfunction, include sensory unawareness, which refers to failure to sense bladder filling and urine flow in the urethra, urinary retention, which is caused by failure to micturate due to inability to relax the EUS in consequence of decision-making disorder, enuresis and nocturia, which occur due to inability to determine the time and place for micturition, and urge incontinence ( Cong et al, 2019 ).…”
Section: Clinical Significancementioning
confidence: 99%
“…Thus, urinary retention/stress incontinence/poor bladder compliance may be induced as a result of lower spinal cord injury or peripheral nerve injury, which causes LMN dysfunction. Detrusor sphincter dyssynyergia, autonomic dysreflexia, and detrusor overactivity may occur in response to UMN dysfunction or cerebral injuries ( Chancellor et al, 2020 ). The problems that can arise as a result of cerebral injuries that cause sensory neuron dysfunction, include sensory unawareness, which refers to failure to sense bladder filling and urine flow in the urethra, urinary retention, which is caused by failure to micturate due to inability to relax the EUS in consequence of decision-making disorder, enuresis and nocturia, which occur due to inability to determine the time and place for micturition, and urge incontinence ( Cong et al, 2019 ).…”
Section: Clinical Significancementioning
confidence: 99%
“…In this study, we evaluated the safety of Autologous Muscle Derived Cells (AMDC) in the treatment of chronic Underactive Bladder (UAB). UAB is caused by deteriorating bladder function with incomplete bladder emptying symptoms including urine frequency, urgency, hesitancy, difficulty starting and/or stopping voiding, incontinence, nocturia, straining to void and recurrent urinary infections [1], [2], [3], [4], [5]. Diokno and associates reported that 22% of men and 11% of women over 60 reported difficulty emptying their bladders [6], [7].…”
Section: Introductionmentioning
confidence: 99%
“…Regenerative medicine approaches have been reported to treat lower urinary tract dysfunction [2]. AMDC are currently under investigation and have been tested in women with stress urinary incontinence [12], [13], [14].…”
Section: Introductionmentioning
confidence: 99%
“…Detrusor underactivity (DU) and its symptom-based correlate underactive bladder (UAB) have gained renewed interest in the past few years [ 1 ]. DU is defined as a contraction of reduced strength and/or duration, resulting in prolonged bladder emptying and/or failure to achieve complete bladder emptying within a normal time span [ 2 ].…”
Section: Introductionmentioning
confidence: 99%